Implementasi Kebijakan Reformasi Birokrasi Bidang Aparatur Sumber Daya Manusia Pada Biro Sumber Daya Manusia Kepolisian Daerah Kalimantan Tengah - Muhaimin Noor; Purwadi Sigit Sulistiyo (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2016)
This study aims to describe and analyze bureaucratic reform in the Human Resources Bureau of the Central Kalimantan Regional Police in the field of human resources. The research method used is descriptive with a qualitative approach. The sources of this research consisted of the Head of the Bureau of Rena, Central Kalimantan Regional Police, and the Head of Sub-Department of Human Resources at the Central Kalimantan Regional Police. Data collection techniques used in the form of interviews, observation and documentation. Data analysis is done by collecting data, reducing data, presenting data and drawing conclusions. The results of this study indicate that the Manuia Resource Bureau of the Central Kalimantan Regional Police has implemented bureaucratic reform in the field of human resources. Berntuk for bureaucratic reform is the presence of the Quick Wins open promotion program. In general, the Quick Wins open promotion program has gone well. According to the results of the analysis using the George Edward III (1980) implementation model, results were obtained: the dimensions of communication consisting of transition, clarity, and consistency of information were good; the resource dimension consists of human / staff resources, budget, facilities, information, and good authority; dimension of disposition, implementation has shown a good attitude; while the dimensions of the bureaucratic structure consisting of SOP and fragmentation are good. But in reality in the field there are a number of interested people for open promotion programs that are still lacking.